Structure and Microwave Dielectric Properties of Low Firing Bi2Te2W3O16 Ceramics. Issue 4 (26th December 2013) - Schileo, Giorgio; Dias, Anderson; Moreira, Roberto L.; Jackson, Tim J.; Smith, Paul A.; Chung, Kelvin T. S.; Feteira, Antonio; Alford, N.
<x xml:space="preserve">Abstract</x> Dense Bi2Te2W3O16 ceramics were prepared by the conventional solid‐state reaction route. X‐ray diffraction data show the room‐temperature (RT) crystal symmetry of Bi2Te2W3O16 to be well described by the centrosymmetric monoclinic C2/c space group [a = 21.280(5) Å, b = 5.5663(16) Å, c = 12.831(3) Å and β = 124.014(19)° and Z = 4]. Raman spectroscopy analyses are in broad agreement with space group assignment, but also revealed the presence of Bi2W2O9 as a secondary phase. This phase is present as plate‐like grains embedded on a fine‐grained equiaxed matrix, as revealed by scanning electron microscopy. From the fitting of infrared reflectivity data the relative permittivity, εr, was estimated as 34.2, and the intrinsic quality factor, Qu × f as 57 500 GHz. At RT and microwave frequencies, Bi2Te2W3O16 ceramics sintered at 720°C for 6 h exhibit εr 34.5, Qu × f = 3173 GHz (at 7.5 GHz), and temperature coefficient of resonant frequency, τf = −92 ppm/°C. This shows a good agreement between the estimated and measured εr values, but also shows that, in principle, the dielectric losses of the ceramics are of extrinsic origin.